Significant Influence of Gamma-Radiation-Treated Chitosan and Alginate on Increased Productivity as Well as Improved Taste and Flavor of Pineapple. (14th September 2020) - Uddin, Ielias; Islam, Jahid M. M.; Haque, Azizul; Zubair, Abu; Barua, Rajesh; Rahaman, Samsur; Rahman, Latifur; Khan, Mubarak A.
ABSTRACT: Many researches have reported plant growth promotion activity of irradiated chitosan and sodium alginate (Na-alginate) individually. However, there is no study on the combined effect of irradiated chitosan and Na-alginate on plant growth and quality of the produces. In this study, individual effects of gamma-radiation-treated chitosan and Na-alginate were compared with the mixed solution of irradiated chitosan and Na-alginate by the means of growth and taste of pineapple. Gamma-irradiated Na-alginate treatment with an interval of 30 days showed maximum plant growth while the best pineapple fruit growth was found for the Na-alginate treatment with an interval of 15 days. On the other hand, gamma-irradiated chitosan treatment showed better fruit quality with respect to taste and flavor. However, in terms of both growth and quality, the mixed solution (90:10 irradiated Na-aliginate:chitosan) was found to be the best. A significant increase of pineapple size, sweetness, aroma, and flavor was recorded in case of the mixed treatment with 30 days of interval.